Covid-19: Perspectives on Innate Immune Evasion - Taefehshokr, Nima; Taefehshokr, Sina; Hemmat, Nima; Heit, Bryan (Frontiers in Immunology, 2020)
The ongoing outbreak of Coronavirus disease 2019 infection achieved pandemic status on March 11, 2020. As of September 8, 2020 it has caused over 890,000 mortalities world-wide. Coronaviral infections are enabled by potent immunoevasory mechanisms that target multiple aspects of innate immunity, with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) able to induce a cytokine storm, impair interferon responses, and suppress antigen presentation on both MHC class I and class II. Understanding the immune responses to SARS-CoV-2 and its immunoevasion approaches will improve our understanding of pathogenesis, virus clearance, and contribute toward vaccine and immunotherepeutic design and evaluation. This review discusses the known host innate immune response and immune evasion mechanisms driving SARS-CoV-2 infection and pathophysiology.